The Liquid Diet Composition Affects the Fecal Bacterial Community in Pre-weaning Dairy Calves - Virgínio Júnior, Gercino Ferreira; Coelho, Marina Gavanski; de Toledo, Ariany Faria; Montenegro, Horácio; Coutinho, Luiz Lehmann; Bittar, Carla Maris Machado (Frontiers in Animal Science, 2021)
Feeding a liquid diet to the newborn calf has considerable implications for developing the intestinal microbiota, as its composition can shift the population to a highly adapted microbiota. Milk acidification may positively affect microorganisms that are beneficial to the intestine's health. The present work evaluated 15 Holstein calves individually housed and fed one of the three liquid diets: I – whole milk (n = 5), II – milk replacer (22.9 % CP; 18.8 % fat; diluted to 14% solids; n = 5) and III - whole milk acidified to pH 4.5 with formic acid (n = 5). All animals received 6 L of liquid diet, divided into two meals, being weaned at week 8 of life. Calves also had free access to water and starter concentrate. After weaning, all calves were grouped housed, fed with starter concentrate, and hay ad libitum. The fecal samples were collected at birth (0) and at weeks 1, 2, 4, 8, and 10 of life. The microbial community was determined by sequencing V3 and V4 region amplicons of the 16S rRNA gene that was amplified by PCR and sequenced by the Illumina MiSeq platform. Diversity indices were not affected by the liquid diets, but by age (P < 0.001) with weeks 1 and 2 presenting lower diversity, evenness, and richness values. The bacterial community structure was affected by diet, age, and the interaction of these factors (P < 0.01). Twenty-eight bacterial phyla were identified in the fecal samples, and the most predominant phyla were Firmicutes (42.35%), Bacteroidota (39.37%), and Proteobacteria (9.36%). The most prevalent genera were Bacteroides (10.71%), Lactobacillus (8.11%), Alloprevotella (6.20%). Over the weeks, different genera were predominant, with some showing significant differences among treatments. The different liquid diets altered the fecal bacterial community during the pre-weaning period. However, differences in the initial colonization due to different liquid diets are alleviated after weaning, when animals share a common environment and solid diet composition.